A global, incremental development method for a web-based prostate cancer treatment decision aid and usability testing in a Dutch clinical setting. (September 2019) - Cuypers, Maarten; Lamers, Romy ED; Kil, Paul JM; The, Regina; Karssen, Klemens; van de Poll-Franse, Lonneke V; de Vries, Marieke
Many new decision aids are developed while aspects of existing decision aids could also be useful, leading to a sub-optimal use of resources. To support treatment decision-making in prostate cancer patients, a pre-existing evidence-based Canadian decision aid was adjusted to Dutch clinical setting. After analyses of the original decision aid and routines in Dutch prostate cancer care, adjustments to the decision aid structure and content were made. Subsequent usability testing (N = 11) resulted in 212 comments. Care providers mainly provided feedback on medical content, and patients commented most on usability and summary layout. All participants reported that the decision aid was comprehensible and well-structured and would recommend decision aid use. After usability testing, final adjustments to the decision aid were made. The presented methods could be useful for cultural adaptation of pre-existing tools into other languages and settings, ensuring optimal usage of previous scientific and practical efforts and allowing for a global, incremental decision aid development process.